A «halfway» policy. Reflections on the policy for Indigenous Peoples of Recent Contact in Brazil - Jabur, Clarisse (2021)
The policy for indigenous peoples of recent contact (PIRC) in Brazil is under construction. Although the guidelines for post-contact periods were present at other moments in government policy, they did not free indigenous peoples from cruel fates such as massacres, epidemics, andtotal extermination. Only after the policy change in 1987 were health measures included in post-contact actions and other actions with an educational bias. In recent years, there have been some advances in internal regulations related to various public policies, highlighting the publication of joint ordinance MS / FUNAI No. 4.094 on health care for indigenous peoples of recent contact. Likewise, the first Territorial and Environmental Management Plans (PGTA) have been formulated by indigenous peoples of recent contact in Brazil. This policy is still «half way» and has some challenges to consolidate.